2011
DOI: 10.1038/onc.2011.171
|View full text |Cite
|
Sign up to set email alerts
|

TP63 P2 promoter functional analysis identifies β-catenin as a key regulator of ΔNp63 expression

Abstract: The DNp63 protein, a product of the TP63 gene that lacks the N-terminal domain, has a critical role in the maintenance of self renewal and progenitor capacity in several types of epithelial tissues. DNp63 is frequently overexpressed in squamous cell carcinoma (SCC) and in some other epithelial tumours. This overexpression may contribute to tumour progression through dominantnegative effects on the transcriptionally active (TA) isoforms of the p53 family (TAp63, TAp73 and p53), as well as through independent me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 45 publications
1
31
0
1
Order By: Relevance
“…Ectopic high levels of p63 expression were able to induce transdifferentiation and squamous metaplasia of mouse lung epithelium [56]. In addition, high p63 levels have been associated with squamous cell carcinoma and β-Catenin has been shown to regulate this protein in this disease [57], [58]. Therefore our studies suggest that stabilized β-Catenin acts to induce high levels of p63, which drives the transdifferentiation process towards a squamous fate.…”
Section: Discussionmentioning
confidence: 55%
“…Ectopic high levels of p63 expression were able to induce transdifferentiation and squamous metaplasia of mouse lung epithelium [56]. In addition, high p63 levels have been associated with squamous cell carcinoma and β-Catenin has been shown to regulate this protein in this disease [57], [58]. Therefore our studies suggest that stabilized β-Catenin acts to induce high levels of p63, which drives the transdifferentiation process towards a squamous fate.…”
Section: Discussionmentioning
confidence: 55%
“…Deregulated expression of Tp63 leading to an increased ΔNp63/Tp63 ratio promotes tumor development by inhibiting cellular senescence 85 . Inactivation of p53 function, combined with the activation of Wnt/β-catenin pathway, results in the overexpression of ΔNp63 that promotes oral mucosal tumorigenesis and early metastatic progression 30, 86 . Furthermore, in squamous cell carcinomas, the transcription factor SOX2, which is critical for the maintenance of embryonic and adult stem cells, preferentially interacts with ΔNp63 and regulates gene expression that governs undifferentiated cancer stem cells-like properties 87 .…”
Section: Discussionmentioning
confidence: 99%
“…We showed previously that ASPP2 partially overlaps with β-catenin at cell-cell junctions and can be detected in the same protein complex (32). A more recent study showed that nuclear β-catenin can directly transactivate ΔNp63 expression (34). We tested whether ASPP2 could repress p63's expression by inhibiting β-catenin-mediated induction of ΔNp63.…”
Section: Aspp2 Represses P63 Expression By Binding Iκb and Inducing Nmentioning
confidence: 96%